2001
DOI: 10.1109/77.919702
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of superconducting properties of Bi-2212 round wire and primary test results of large capacity Rutherford cable

Abstract: We have developed HTS cables using Bi-2212 round wires, which have high mechanical strength and an average J, of 200kA/cm2 at 4.2K in self-field. Four designs of cables were fabricated in this work and those cables could carry I, values from 1kA to lOkA at 4.2K and self-field depending on the number of strands. A 70m-long 20-strand Rutherford cable was successfully manufactured. Optimization of heat treatment conditions was effective to reduce I, degradation observed in the case of heat treatment with a long l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 3 publications
0
33
2
Order By: Relevance
“…The main attractiveness of Bi-2212, besides the highfield properties recalled above, is that it is available as a round wire, and can thus be formed into a Rutherford cable, as has been consistently demonstrated since the 1990s [113][114][115][116]. The record J E is around 500 A/mm 2 at 20 T, 4.2 K in a 1-m-long round wire [117] (Fig.…”
Section: Bi-2212mentioning
confidence: 86%
See 1 more Smart Citation
“…The main attractiveness of Bi-2212, besides the highfield properties recalled above, is that it is available as a round wire, and can thus be formed into a Rutherford cable, as has been consistently demonstrated since the 1990s [113][114][115][116]. The record J E is around 500 A/mm 2 at 20 T, 4.2 K in a 1-m-long round wire [117] (Fig.…”
Section: Bi-2212mentioning
confidence: 86%
“…The concept of Rutherford cables can be easily applied to any material that comes in the form of round wires, and it has been extended to round Bi-2212 HTS wires [113][114][115][116]. Further cable concepts, such as the Roebel bar, or tape assemblies around a stabilizer core or tube, discussed earlier, are in an early stage of development and have not yet found an accelerator application.…”
Section: Superconducting Materials and Conductors: Fabrication And LImentioning
confidence: 99%
“…It has been already demonstrated that such properties make Bi-2212 a very competitive conductor for high field applications (> 20 T) such as magnets for nuclear magnetic resonance or accelerators [4][5][6][7][8][9], however, in this context, an enhancement of J C of two or three times seems to be still needed to boost the successful use of this superconductor in such applications. This aim has driven the work of several groups, especially in USA -where, besides the research labs, Oxford Superconducting Technology (OST) is a company leader on Bi-2212 round wire fabrication -and in Japan and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The filament mass density was calculated by assuming the density of silver and silver alloy to be 10.49 g/cm 3 . X-ray tomographic 2 . More details about the tomography set-up can be found in [11].…”
mentioning
confidence: 99%